Current status and focus of breast reconstruction research in China and abroad: a bibliometric study - REN Hengyu, HAO Shuang, CHEN Jiajian, YANG Benlong, CAO Ayong, LIU Guangyu, SHAO Zhimin, WU Jiong (Zhongguo aizheng zazhi, 2023)
Background and purpose: According to the 2020 global cancer burden data of the International Agency for Research on Cancer (IARC), breast cancer has replaced lung cancer as the most common type of cancer worldwide. The aim of this study was to conduct a bibliometric and visual analysis of breast reconstruction related research in China and abroad published in the past 5 years, to understand the research status and development trend in this field, to discuss the focus of research in different countries and different disciplines, and to provide reference for other researchers. Methods: Relevant literatures about breast reconstruction were retrieved from the Web of Science Core Collection. The VOS viewer 1.6.15 software was used to extract the authors, countries, institutions and keywords to generate network maps of high-yield authors, institutions and high-frequency keywords clustering network. Results: A total of 4 815 documents meeting the requirements were retrieved, which showed an upward trend in the past five years. Regarding the discipline, 838 documents (17.40%) were published by breast surgery and Cancer Surgery, 3 308 (68.70%) were published by plastic surgery, and 669 (13.90%) were jointly published by both types of researchers. There were differences in the disciplines of the main authors between China and abroad. In China, authors from breast surgery published a larger proportion of documents (138, 44.52%), while the number of documents published by authors of plastic surgery (129, 44.52%) and the joint publication of both types of authors (43, 13.87%) was relatively small. However, foreign documents mainly came from authors of plastic surgery (74.74%). There were more cooperative groups (155) formed by major foreign authors, and more frequent joint publishing between groups, while Chinese authors formed only 16 cooperative groups with less cooperation. Authors from breast surgery focused more on oncology-related issues in breast reconstruction, while in plastic surgery, more attentions were paid on autologous tissue reconstruction. Conclusion: Breast reconstruction has gradually attracted the attention of Chinese and foreign researchers. Compared with foreign countries, there were problems such as lack of high-quality research and less cooperative research in China. There were differences in the research focus of breast reconstruction between China and abroad, which was mainly related to the differences in the disciplines of researchers.